2016
DOI: 10.7439/ijbar.v7i5.3267
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and skinfold thickness measurements as indicators of obesity in adolescents

Abstract: Objective: To assess prevalence of overweight and obesity in government and private school adolescents by using BMI and measurements of skinfold thickness as parameter of obesity and to evaluate diagnostic value of skinfold thickness measurement as compared to BMI in identifying overweight and obese adolescents. Methods: This was questionnaire based, voluntary response prospective study. Data were collected from 600 adolescents aged between 10-19 years divided equally between government and private school of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…13 Eyes were pale in 25.4% and 11.8% had flat nails in Shivaprakash and Joseph study in urban area which was higher compared to our study where 19.44% of urban adolescent eyes were pale and 1.67% had flat nails. 10,11 Underweight finding inour study was similar to Deshmukh PR et al (75.3%), less compared to Srinivasan K et al (78.4%), whereas higher than Rao V G et (61.7%) and Pal A et al (48.78%). 6,9,14,15…”
Section: Discussionsupporting
confidence: 79%
“…13 Eyes were pale in 25.4% and 11.8% had flat nails in Shivaprakash and Joseph study in urban area which was higher compared to our study where 19.44% of urban adolescent eyes were pale and 1.67% had flat nails. 10,11 Underweight finding inour study was similar to Deshmukh PR et al (75.3%), less compared to Srinivasan K et al (78.4%), whereas higher than Rao V G et (61.7%) and Pal A et al (48.78%). 6,9,14,15…”
Section: Discussionsupporting
confidence: 79%
“…18,19 We found that in all study participants i.e. 24, BMI correlates significantly with triceps skin fold thickness Spearman's r=0.53, p=0.006 which is in accordance with studies done by Mehru et al, Khadilkar et al, Robert et al [20][21][22] However, this finding is not consistent with findings of Rolland et al and Rona et al which showed weak correlation. 23 Among males BMI correlates significantly with triceps skin fold thickness Spearman's r=0.64, p=0.01.…”
Section: Discussionsupporting
confidence: 60%
“…10,11 BMI is a measure of body weight, and therefore doesn't make allowances for increased weight due to muscular development.…”
Section: Discussionmentioning
confidence: 99%